Inflammatory Lesion Patterns in Target Organs of Visna/Maedi in Sheep and their Significance in the Pathogenesis and Diagnosis of the Infection. (February 2018) - Gayo, E.; Polledo, L.; Balseiro, A.; Martínez, C.Pérez; García Iglesias, M.J.; Preziuso, S.; Rossi, G.; García Marín, J.F.
Summary: Ovine visna/maedi (VM) infection is characterized by the development of chronic inflammatory lesions in different organs, mainly in the lung, mammary gland and central nervous system (CNS), with either histiocytic or lymphocytic pattern predominance being described in the CNS. To help to understand the role of host immune response in the development of these patterns, 50 naturally-infected sheep and eight non-infected sheep from intensive milk-producing flocks were studied. The histological lesion patterns in the three main target organs in each sheep were characterized. Lesion severity was determined, including minimal lesions. A histiocytic pattern was observed in 23 sheep (46%), a lymphocytic inflammatory pattern in 19 sheep (38%) and a mixed inflammatory pattern in eight sheep (16%). Forty animals showed moderate or severe lesions (80%), while 10 had minimal lesions (20%). Moderate or severe lesions affected only one target organ in 20 sheep (50%), two organs in 14 sheep (35%) and all three target organs in six sheep (15%). Infection was confirmed by immunohistochemistry (IHC) using an antibody specific for p28 of VM virus/caprine arthritis and encephalitis virus and by polymerase chain reaction (PCR) in all sheep. Minimal inflammatory lesions associated with positive IHC and PCR were observed. The results suggest that the development of a predominant inflammatory pattern in different organs within the same animal may be related to the host immune response. Minimal and focal lesions, not considered previously, should be taken into account when formulating a differential diagnosis in affected sheep.